Comprehensive techno-economic analysis of wastewater-based algal biofuel production: A case study. (July 2016) - Xin, Chunhua; Addy, Min M.; Zhao, Jinyu; Cheng, Yanling; Cheng, Sibo; Mu, Dongyan; Liu, Yuhuan; Ding, Rijia; Chen, Paul; Ruan, Roger
Highlights: Innovative pathway assessment was carried based on the pilot-scale testing data. The TEA result showed the break even selling price of biofuel was 2.23/gallon. The IRRs of the process and system were between −6.1% and 18.7%. Abstract: Combining algae cultivation and wastewater treatment for biofuel production is considered the feasible way for resource utilization. An updated comprehensive techno-economic analysis method that integrates resources availability into techno-economic analysis was employed to evaluate the wastewater-based algal biofuel production with the consideration of wastewater treatment improvement, greenhouse gases emissions, biofuel production costs, and coproduct utilization. An innovative approach consisting of microalgae cultivation on centrate wastewater, microalgae harvest through flocculation, solar drying of biomass, pyrolysis of biomass to bio-oil, and utilization of co-products, was analyzed and shown to yield profound positive results in comparison with others. The estimated break even selling price of biofuel (2.23/gallon) is very close to the acceptable level. The approach would have better overall benefits and the internal rate of return would increase up to 18.7% if three critical components, namely cultivation, harvest, and downstream conversion could achieve breakthroughs.